2019
DOI: 10.1093/neuonc/noz126.000
|View full text |Cite
|
Sign up to set email alerts
|

PL1.1 CDKN2A homozygous deletion is a strong adverse prognosis factor in diffuse malignant IDHmutant gliomas

Abstract: The 2016 WHO classification of the central nervous system tumors stratifies diffuse adult gliomas into three major groups depending on the presence or absence of two main genetic alterations: IDH mutation and 1p/19q-codeletion. However, the grading system initially based on histological criteria remains unchanged and it is now controversial whether it can be still applied to this updated molecular classification. Therefore, in a large cohort of 911 high grade IDH-mutant gliomas from the French national POLA ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(40 citation statements)
references
References 0 publications
2
36
2
Order By: Relevance
“…These tumors have more frequent instances of chromothripsis [52,67], increased frequency of mutation in genes responsible for overall genomic stability [52], and increased frequency of CDK4 and CDKN2A/B alterations than their IDH-mutant lower-grade glioma counterparts, which corresponds to their worse clinical outcomes in terms of PFS and OS, but unlike within the lower-grade cohorts, we found no statistically significant prognostic effect of harboring these alterations in GBM [52]. Other groups have shown that MET amplification, PDGFRA amplification, and CDKN2A deletion are associated with poor prognosis within some IDH-mutant GBM cohorts [47,72,75,94]. Additional less-studied proposed factors include nuclear transcription factors that regulate cellular defense against oxidative damage, such as SNRX1, NRF2, and DJ2, which may have prognostic implications in IDH-mutant GBM cohorts in addition to IDH-mutant lower-grade astrocytomas [55].…”
Section: Idh-mutant Glioblastomacontrasting
confidence: 51%
See 3 more Smart Citations
“…These tumors have more frequent instances of chromothripsis [52,67], increased frequency of mutation in genes responsible for overall genomic stability [52], and increased frequency of CDK4 and CDKN2A/B alterations than their IDH-mutant lower-grade glioma counterparts, which corresponds to their worse clinical outcomes in terms of PFS and OS, but unlike within the lower-grade cohorts, we found no statistically significant prognostic effect of harboring these alterations in GBM [52]. Other groups have shown that MET amplification, PDGFRA amplification, and CDKN2A deletion are associated with poor prognosis within some IDH-mutant GBM cohorts [47,72,75,94]. Additional less-studied proposed factors include nuclear transcription factors that regulate cellular defense against oxidative damage, such as SNRX1, NRF2, and DJ2, which may have prognostic implications in IDH-mutant GBM cohorts in addition to IDH-mutant lower-grade astrocytomas [55].…”
Section: Idh-mutant Glioblastomacontrasting
confidence: 51%
“…Relatively frequent gains in 7p and 11p as well as losses in 14q and 15q were associated with worse outcome and tumor progression, as were alterations in the Notch pathway and PI3K-AKT pathway, NOTCH1, PIK3CA, PIK3R1, and ARID1A [36,45,93]. Like their astrocytic counterparts, homozygous loss of CDKN2A has also been associated with poor outcomes in patients with anaplastic oligodendroglioma [94]. A number of studies have also shown that the polysomy of chromosomes 1 and 19 (defined as >2 signals detected by FISH for both 1q and 19p in 1p/19q co-deleted tumors) was associated with higher histologic grade, earlier recurrence, and worse patient outcomes compared to oligodendrogliomas without polysomy, although the negative impact on overall survival was not seen in all studies [95][96][97][98].…”
Section: Oligodendrogliomamentioning
confidence: 97%
See 2 more Smart Citations
“…In the previous literature, there were inconsistent findings on whether a CDKN2A homozygous deletion was associated with poor survival in IDH-mutant and 1p/19q-codeleted ODGs [4,8,28]. Similarly, our study did not show any prognostic significance of p16 protein loss in ODG.…”
Section: Discussioncontrasting
confidence: 84%